The Effect of Emotional Intelligence and Learning Style on Biology Learning Outcomes of Class XI MIPA Students at SMA Negeri 4 Jember Academic Year 2022/2023 - Permatasari, Amalia Dewi; Nurlim, Risma; Nurlim, Idiawati (META: Journal of Science and Technological Education, 2024)
In the context of education in Indonesia, particularly in schools, a prevalent problem persists wherein a significant number of students exhibit a lack of concentration towards their studies and instead engage in various extracurricular pursuits. The objective of this study is twofold: To determine the combined impact of emotional intelligence and learning styles on the biology learning outcomes; and to ascertain the individual effects of emotional intelligence and learning styles on the biology learning outcomes. This study employs a quantitative methodology utilizing survey research techniques conducted at SMA Negeri 4 Jember. The researcher employed Arikunto's sampling technique, which states that if the number of participants is fewer than 100, the entire population can be considered as the research sample. In this study, a sample of 60 pupils was taken. Data collecting methods employ surveys and documentation, while data analysis involves the utilization of multiple linear regression. The research findings indicate that the F count value of 11.532 is statistically higher than the F table value of 3.16. Therefore, it can be concluded that the combination of emotional intelligence and learning style has a significant impact on the biology learning outcomes of class XI MIPA students at SMA Negeri 4 Jember. Furthermore, the emotional intelligence (tcount 2,968 > ttable 1,672) and learning styles (tcount 2,849 > ttable 1,672) individually also has a direct influence on the biology learning outcomes of class XI MIPA students at SMA Negeri 4 Jember.